The First World War in the Mar Piccolo of Taranto: First case of warfare ecology?. (15th November 2017) - Caroppo, Carmela; Portacci, Giuseppe
Abstract: Since 1883, the Mar Piccolo of Taranto (Ionian Sea, Mediterranean) has played a dual role as privileged area for shellfish farming and strategic military port. In the early 1900, the basin already showed some serious environmental and production management deficiencies, stressed by the First World War. This historical research, based on the collection of direct, indirect and iconographic sources, provided socioeconomic information about Taranto from 1883 to 1926 and unprecedented data on the most probable catastrophic effects (the sinking of a dreadnought) on the marine environment during the First World War. Moreover, the study demonstrated that the holistic approach followed by the Marine Biology Laboratory's Inspector (Attilio Cerruti) for the management of shellfish farming could be assimilated to current 'warfare ecology'. He had to face disastrous effects on the environment jeopardising ancient farming activities. He therefore carried out actions to reduce, mitigate, and prevent warfare effects. The analysis of original documents showed that the strategies (scientific studies, application and propagation of best practices; economic evaluation of productions; communication with military and civil authorities and shellfish farmers) adopted by Cerruti ensured shellfish farming survival and its recovery in the post war period. Moreover, Cerruti's warfare ecology approach could be a useful example for the solution of current management and conservation problems related to goods and services of valuable ecosystems highly impacted by human activities (not limited to warfare), such as those affecting the Mar Piccolo of Taranto. Graphical abstract: Highlights: Management of mariculture in the heavy impacted Mar Piccolo during the Great War. Review of socioeconomic and environmental data from various historical sources. Environmental disaster: warfare and explosion, sinking and cratering of a warship. Demonstration of ante litteram warfare ecology and post-conflict risk assessment. Historical knowledge to provide input to management and conservation policies.